1961
DOI: 10.1063/1.1701219
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Synthetic Crystalline Zeolites

Abstract: The electrical conductivity of anhydrous Linde zeolite types A, X, and Y in various cationic forms has been measured between 20 and 400°C. The conductivity is ohmic, essentially noncapacitive, and appears to be strictly ionic with unusually low activation energy. From the effect of zeolite channel size, type of cation and cation density on ΔH, ΔG, and ΔS for the conduction process, some conclusions as to the zeolite internal structure and surface energy have been obtained. The heterogeneity of the internal sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(70 citation statements)
references
References 7 publications
7
63
0
Order By: Relevance
“…By irradiation of zeolites and zeolite-like materials, it is possible to change their granular structure, to form non-equilibrium electrons and holes, and different type of radicals on the samples surface [23,24]. All listed processes may result in a change of parameters for electrical-carrier transport of zeolite, such as concentration of protons and their mobility, length of free path of charge carriers (various ions), and polarization of the crystal cage [20,25]. Fig.…”
Section: Specific Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…By irradiation of zeolites and zeolite-like materials, it is possible to change their granular structure, to form non-equilibrium electrons and holes, and different type of radicals on the samples surface [23,24]. All listed processes may result in a change of parameters for electrical-carrier transport of zeolite, such as concentration of protons and their mobility, length of free path of charge carriers (various ions), and polarization of the crystal cage [20,25]. Fig.…”
Section: Specific Conductivitymentioning
confidence: 99%
“…The main reason for such relaxation is the polarization of a sample, which is taken into account by a method described in refs. [17][18][19][20].…”
mentioning
confidence: 99%
“…Similar behavior is to be expected in the variation with Al-content of the thermal stability of the NH4*-exchanged faujasite series. Stamires (1960Stamires ( , 1962; Freeman and Stamires (1961 );Schoonheydt and Uytterhoeven (1969) have shown that the current-carrying species in synthetic zeolites are cations migrating in the structure by a "jump" mechanism. Further, the activation energy for conduction is due to the electrostatic interaction of the cation with its site in the alumino--silicate framework.…”
Section: Mechanism Of Structural Degradation By Steamingmentioning
confidence: 99%
“…Ducros and Rimsky (176) claim that the Ca++ ions in hydrated natural chabazite are situated near the centres of the hexagonal prisms at the top and bottom of each cage, They were unable to place the This is probably due to the additional loss contribution from the increased number of water molecules, to the lowering of the energy barrier to cation migration and to a wider distribution of relaxation times. It is (160,161,165,168) …”
Section: Use Of Bottoberis Equationmentioning
confidence: 99%